ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR BERAS DI INDONESIA DENGAN PENDEKATAN PARTIAL LEAST SQUARE (PLS) - Febiyola, Febiyola; Yanita, Mirawati (JALOW | Journal of Agribusiness and Local Wisdom, 2019)
As a producer of rice, Indonesia still import rice to meet domestic rice consumption. This is not appropriate with data that shows that domestic rice production has a surplus. Surplus rice production, the government should be able to meet domestic demand for rice without the need to import rice. Therefore, this study aims to: 1) describe the development of rice imports in Indonesia and the factors that influence them, 2) analyze the factors that influence rice imports in Indonesia. Variables used in this research are inflation, gross domestic product, land area, rice production, direct and indirect consumption, supply of rice, population, domestic rice prices, exchange rate and world rice prices period 1996-2016. The data used are secondary data obtained from FAO, COMTRADE UN, BPS and Directorate General of Food. The analytical method used is an approach using Partial Least Square (PLS). The results showed that rice imports in Indonesia fluctuate tend to increase due to the influence of macroeconomic variables with moderating variables, both directly and indirectly. Macroeconomic variables with moderating variables in rice farming have no significant effect on rice imports. While macroeconomic variables with moderating variables demand for rice significantly influence rice imports. Macroeconomic variables directly influence the import of rice. Kata Kunci: Impor, Makro Ekonomi, Usahatani Padi, Permintaan Beras